Legal Synergy for Notary Deed Updating in the Field of Intellectual Property Rights - Mirza Alvina Maharani (Sean Institute, 2024)
Legal Synergy in the modernization of the notarial deed drafting process within the scope of Intellectual Property Rights (IPR) is a critical aspect of legal development in Indonesia. Along with the growth of the creative economy and business sectors, the demand for more effective protection of intellectual works continues to rise. This article aims to analyse the steps involved in drafting notarial deeds related to IPR, as well as the role of notaries in supporting the protection of intellectual property rights. The research was conducted using normative juridical methods, employing statutory and conceptual approaches, and utilizing primary, secondary, and tertiary legal materials. The results show that the IPR legal system in Indonesia is still fragmented, which makes it difficult for notaries to prepare deeds that are in accordance with all applicable provisions. Integrated guidelines and closer cooperation with the DJKI are needed to improve efficiency, legal certainty, and IPR protection for the community.